Management Strategies in Basic Education and Participation of Parents - Johel Furguerle-Rangel; José Gregorio Pacheco-Barrio; Alba Hernández; Gilberto Bastidas-Pacheco (Revista Electrónica Educare)
In the educational process it is necessary to use management paradigms and active participation of parents. The objective was to determine the use of management strategies by the director of basic education and participation of parents in the educational process. It is a descriptive, transversal and field study, whose instrument was a questionnaire of 26 closed-questions.   The sample comprised 16 directors, 52 teachers and 62 parents. For most managers and faculty the technique of brainstorming, involvement in decision-making, continues knowledge management and radical change are crucial in the educational process of children.   But mothers and fathers believe that managerial groups do not use strategies properly except for reengineering.   The mother and fathers are mainly involved in education management but not in the learning process. It is recommended the deepening of policy management training teaching force, through continuous training provided by the government and the promotion of family participation in the teaching-learning process of children.